Environmental damage and price taking behaviour by firms and consumers - Harold Houba; Hans Kremers (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Integrated assessment models lack a microeconomic foundation in modelling environmental damages to the economy. To overcome this, damage coefficients are incorporated in standard microeconomic models. Firms and consumers take both damages and prices as given. Demand, supply, profit and expenditure functions under damage coefficients are derived that allow easy implementation in applied economic models through appropriate price distortions related to such coefficients. For the consumer, Slutsky's equations are derived. The different speeds of equilibrium adjustment in economic and climate models is reconciled in the Recursive Equilibrium with Environmental Damages (REED). An exchange economy and Robinson Crusoe economy illustrate our approach.
Keywords: Q41; Q51; Q52; D11; D12; D51; 330; Environmental damage; substitution effects; income effects; Slutsky's equations; equilibrium; Umweltbelastung; Mikroökonomik; Substitutionseffekt; Einkommenseffekt; Klimaschutz; Gleichgewichtstheorie; Theorie